Single-crystal layered oxide positive electrode material, preparation method thereof and sodium ion battery
Through spray drying and two sintering treatments, large-size single-crystal layered oxide positive electrode material was prepared, solving the problems of complex sulfate agglomeration and preparation process, and achieving the improvement of the material's stability and discharge capacity.
Patent Information
- Application Number
- CN202411522789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The prior art faces the problems of serious sulfate aggregation, complex preparation process and high cost when preparing the positive electrode material of layered transition metal sodium ion battery.
The mixed metal sulfate solution was used for spray drying and pre-treatment, and a large-size single-crystal layered oxide positive electrode material was prepared through two sintering treatments to avoid the influence of sulfate agglomeration.
The stability and discharge capacity of single-crystal layered oxide positive electrode material are improved, the production cost is reduced, and the technical problems of sulfate agglomeration are avoided.
Smart Images

Figure CN119390140A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a single crystal layered oxide positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Lithium-ion batteries have become dominant in portable electronic devices and new energy vehicles. As one of the important raw materials for lithium-ion batteries, lithium prices have recently been subject to periodic price fluctuations, so people are working hard to find a next-generation electrochemical energy storage technology that can replace lithium-ion batteries, can be applied on a large scale, and is environmentally friendly. Sodium and lithium are in the same main group, have many similar physical and chemical properties, and have much higher reserves than lithium, which gives sodium-ion batteries an advantage in raw material supply, thereby helping to reduce production costs and reduce dependence on lithium resources.
[0003] The cathode material of sodium-ion batteries is one of the main factors that determine battery performance and cost. It mainly includes three categories: Prussian blue compounds, layered transition metal compounds and polyanionic compounds. Among them, layered transition metal compounds have outstanding advantages in energy density, cycle life and material cost, and are the cathode materials with the most promising industrialization prospects. At present, layered transition metal compounds are mostly prepared by co-precipitation to obtain precursors, and then the precursors and sodium sources are mixed and sintered to obtain them. The process of the above-mentioned preparation method is controllable, and the obtained precursor is a compact sphere, so it has a higher tap density. Nevertheless, due to the large number of parameters that need to be regulated in the preparation process and the large differences in the solubility product constants of different metal ions, it is difficult to synthesize uniform and stable layered transition metal compound sodium-ion battery cathode materials.
[0004] In addition, in terms of raw material selection, on the one hand, since metal oxides / hydroxides are insoluble in water, they cannot be directly prepared using the liquid phase method and require long-term high-speed grinding before use. On the other hand, some metal nitrates are dangerous (for example, nickel nitrate is included in the "List of Dangerous Chemicals that Can Be Exploded") and are expensive, so they are not suitable for large-scale production. Although metal chlorides have good dispersibility, they have severe hydrolysis, which easily leads to strong acidity of the salt solution, and the radius of chloride ions is small, which can destroy the passivation film on the surface of 304 stainless steel (stainless steel materials commonly used in equipment). In contrast, metal sulfates are less corrosive to 304 stainless steel, but they easily absorb water, resulting in agglomeration between particles. At present, there are few studies on the preparation of layered sodium ion battery positive electrode materials using metal sulfates as raw materials.
[0005] Therefore, in the art, there is an urgent need to develop a method for preparing layered transition metal sodium ion battery positive electrode materials using metal sulfate as raw material to solve the above problems. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a single crystal layered oxide positive electrode material and a preparation method thereof and a sodium ion battery. The present invention first uses a mixed metal sulfate solution as a raw material for spray drying pretreatment, and then uses two sintering processes to prepare a large-size single crystal layered oxide sodium ion battery positive electrode material, thereby avoiding the technical problem of serious sulfate agglomeration.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a single crystal layered oxide positive electrode material, the method comprising the following steps:
[0009] Preparing a mixed metal sulfate solution containing different metal elements; spray drying the mixed metal sulfate solution to obtain a mixed metal sulfate powder;
[0010] The mixed metal sulfate powder is subjected to a sintering treatment to obtain a mixed metal oxide precursor;
[0011] The mixed metal oxide precursor and the sodium source are subjected to secondary sintering treatment to obtain the single crystal layered oxide positive electrode material.
[0012] Firstly, the present invention selects easily available sulfate solutions containing different metal elements as raw materials, because sulfate ions are not only much less corrosive to stainless steel substrates than chloride ions, but also have cost advantages; secondly, the present invention uses a simple and fast spray drying technology to mix and granulate the mixed metal sulfate solution, so that the prepared mixed metal sulfate powder has uniform composition, which is conducive to the formation of a micron-level single crystal structure in the subsequent primary sintering process; in addition, the single crystal layered oxide positive electrode material prepared by the present invention through the secondary sintering treatment eliminates the influence of sulfate easily absorbing water and agglomerating, and there is no grain boundary inside the single crystal layered oxide positive electrode material, so that its structural stability is higher than that of the polycrystalline positive electrode material, and at the same time, its discharge capacity is close to that of the positive electrode material prepared with chloride as the raw material.
[0013] Preferably, the chemical formula of the single crystal layered oxide positive electrode material is Na a M x N 1-xO2, wherein M is a combination of any two or three of Ni, Fe or Mn, and N is a combination of any one or more of Li, Mg, Al, Si, K, Ca, Ti, V, Cr, Co, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, In, Sn, Sb, W, Ta, Ba, Bi, La, Ce or Eu; 0.7<a≤1.2, a can be, for example, 0.8, 0.9, 1, 1.1, 1.2, etc.; 0.8≤x≤1, x can be, for example, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1, etc.
[0014] Preferably, the concentration of the mixed metal sulfate solution is 1 mol / L to 4 mol / L, preferably 3 mol / L, for example, it can be 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 2.8 mol / L, 3 mol / L, 3.2 mol / L, 3.5 mol / L, 3.8 mol / L, 4 mol / L, etc.
[0015] Preferably, the air inlet temperature of the spray drying is 180°C to 220°C, preferably 200°C, for example, it can be 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, etc.
[0016] Preferably, the outlet temperature of the spray drying is 90°C to 130°C, preferably 100°C, for example, it can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, etc.
[0017] In the present invention, by regulating the air inlet temperature and the air outlet temperature of the spray drying, the water in the solution can be rapidly vaporized and extracted, and the sulfate can form spherical particles with uniform composition.
[0018] Preferably, the particle size of the mixed metal sulfate powder is 0.5 μm to 3 μm, for example, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, etc. The present invention is beneficial to forming a micron-level single crystal structure in a subsequent sintering process by regulating the particle size of the mixed metal sulfate powder.
[0019] Preferably, the primary sintering process is performed in an atmosphere containing oxygen.
[0020] Preferably, the temperature of the primary sintering treatment is 700°C to 1000°C, preferably 900°C; for example, it can be 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, etc.
[0021] Preferably, the time of the primary sintering treatment is 1 h to 5 h, preferably 2 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, etc. The present invention adjusts the process parameters of the primary sintering treatment so that the sulfate can be completely decomposed to obtain a metal oxide precursor with a low sulfur content.
[0022] Preferably, the secondary sintering process is performed in an atmosphere containing oxygen.
[0023] Preferably, the temperature of the secondary sintering treatment is 800℃~1100℃, for example, it can be 800℃, 820℃, 850℃, 880℃, 900℃, 920℃, 950℃, 980℃, 1000℃, 1020℃, 1050℃, 1080℃, 1100℃, etc.; the time is 5h~15h, for example, it can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.
[0024] Preferably, the sodium source includes any one of sodium hydroxide, sodium carbonate, sodium formate or sodium acetate.
[0025] Preferably, the molar ratio of the sodium source to the mixed metal oxide precursor is (1.01-1.07):1, for example, it can be 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, etc.
[0026] In a second aspect, the present invention provides a single-crystalline layered oxide positive electrode material, wherein the single-crystalline layered oxide positive electrode material is prepared by the method for preparing a single-crystalline layered oxide positive electrode material according to the first aspect.
[0027] Preferably, the particle size of the single-crystalline layered oxide positive electrode material is 5 μm to 15 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.
[0028] The preparation method provided by the present invention can prepare a large-sized single-crystal layered oxide sodium ion battery positive electrode material, avoiding the influence caused by water absorption and agglomeration between precursor raw material particles.
[0029] In a third aspect, the present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the single crystal layered oxide positive electrode material according to the second aspect.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention provides a method for preparing a single-crystal layered oxide positive electrode material. Firstly, the present invention selects a sulfate solution containing different metal elements that is easily available as a raw material, because sulfate ions are not only much less corrosive to a stainless steel substrate than chloride ions, but also have a cost advantage; secondly, the present invention utilizes a simple and fast spray drying technology to mix and granulate a mixed metal sulfate solution, so that the prepared mixed metal sulfate powder has uniform components, which is conducive to forming a micron-level single crystal structure in a subsequent primary sintering process; in addition, the single-crystal layered oxide positive electrode material prepared by the present invention through a secondary sintering treatment eliminates the influence of sulfate absorbing water and agglomerating, and there is no grain boundary inside the single-crystal layered oxide positive electrode material, so that its structural stability is higher than that of a polycrystalline positive electrode material, and at the same time, its discharge capacity is close to that of a positive electrode material prepared using chloride as a raw material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM characterization image of the mixed metal sulfate powder provided in Example 1;
[0033] Figure 2 The SEM characterization image of the mixed metal oxide precursor provided in Example 1;
[0034] Figure 3 This is a SEM characterization image of the single crystal layered oxide positive electrode material provided in Example 1;
[0035] Figure 4 The SEM characterization image of the mixed metal chloride powder provided for Comparative Example 1;
[0036] Figure 5 The SEM characterization image of the mixed metal oxide precursor provided for Comparative Example 1;
[0037] Figure 6 This is the SEM characterization image of the single crystal layered oxide positive electrode material provided for Comparative Example 1.
[0038] Figure 7 This is the XRD pattern of the sample provided for Comparative Example 3. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] Example 1
[0041] This embodiment provides a single crystal layered oxide positive electrode material and a preparation method thereof, the preparation method comprising the following steps:
[0042] 0.6 mol NiSO4, 1.05 mol FeSO4, 1.05 mol MnSO4 and 0.3 mol CuSO4 are added to 1 L of water to obtain a mixed metal sulfate solution; the mixed metal sulfate solution is spray-dried to obtain a mixed metal sulfate powder with a particle size of 1 μm, such as Figure 1 As shown, it is denoted as NFMCSO4, where the air inlet temperature is 200°C and the air outlet temperature is 100°C;
[0043] In a compressed air atmosphere, the mixed metal sulfate powder is sintered at 900°C for 2 h to obtain a mixed metal oxide precursor, such as Figure 2 As shown, it is recorded as NFMCO-SO4;
[0044] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate were subjected to secondary sintering treatment at 900° C. for 8 h, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor was 1.03:1, to obtain the single crystal layered oxide positive electrode material having the structural formula of Na 0.98 Ni 0.2 Fe 0.35 Mn 0.35 Cu 0.1 O2, recorded as NaNFMC-SO4.
[0045] The SEM image of the single crystal layered oxide positive electrode material in this embodiment is as follows Figure 3 As shown, it is a single crystal layered positive electrode material with a diameter of 10 μm. In this embodiment, the single crystal layered oxide positive electrode material is tested for the content of each metal atom using inductively coupled plasma (ICP) technology. The content of each metal atom is close to the feed ratio. The test results are shown in Table 1:
[0046] Table 1
[0047]
[0048]
[0049] Example 2
[0050] This embodiment provides a single crystal layered oxide positive electrode material and a preparation method thereof, the preparation method comprising the following steps:
[0051] 0.6 mol of NiSO4, 1.05 mol of FeSO4, 1.05 mol of MnSO4 and 0.3 mol of CuSO4 are added to 1 L of water to obtain a mixed metal sulfate solution; the mixed metal sulfate solution is spray-dried to obtain a mixed metal sulfate powder with a particle size of 1 μm, wherein the air inlet temperature is 200° C. and the air outlet temperature is 100° C.;
[0052] The mixed metal sulfate powder was sintered at 850° C. for 2 h in a compressed air atmosphere to obtain a mixed metal oxide precursor;
[0053] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate were subjected to a secondary sintering treatment at 900° C. for 8 hours, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor was 1.03:1, to obtain the single crystal layered oxide positive electrode material.
[0054] Example 3
[0055] This embodiment provides a single crystal layered oxide positive electrode material and a preparation method thereof, the preparation method comprising the following steps:
[0056] 0.6 mol of NiSO4, 1.05 mol of FeSO4, 1.05 mol of MnSO4 and 0.3 mol of CuSO4 are added to 1 L of water to obtain a mixed metal sulfate solution; the mixed metal sulfate solution is spray-dried to obtain a mixed metal sulfate powder with a particle size of 1 μm, wherein the air inlet temperature is 200° C. and the air outlet temperature is 100° C.;
[0057] The mixed metal sulfate powder was sintered at 950° C. for 2 h in a compressed air atmosphere to obtain a mixed metal oxide precursor;
[0058] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate were subjected to a secondary sintering treatment at 900° C. for 8 hours, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor was 1.03:1, to obtain the single crystal layered oxide positive electrode material.
[0059] Example 4
[0060] This embodiment provides a single crystal layered oxide positive electrode material and a preparation method thereof, the preparation method comprising the following steps:
[0061] 0.6 mol of NiSO4, 1.05 mol of FeSO4, 1.05 mol of MnSO4 and 0.3 mol of CuSO4 are added to 1 L of water to obtain a mixed metal sulfate solution; the mixed metal sulfate solution is spray-dried to obtain a mixed metal sulfate powder with a particle size of 0.5 μm, wherein the air inlet temperature is 180° C. and the air outlet temperature is 90° C.;
[0062] In a compressed air atmosphere, the mixed metal sulfate powder is subjected to a sintering treatment at 700° C. for 5 h to obtain a mixed metal oxide precursor;
[0063] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate are subjected to a secondary sintering treatment at 800° C. for 8 hours, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor is 1.03:1, to obtain the single crystal layered oxide positive electrode material.
[0064] Example 5
[0065] This embodiment provides a single crystal layered oxide positive electrode material and a preparation method thereof, the preparation method comprising the following steps:
[0066] 0.6 mol of NiSO4, 1.05 mol of FeSO4, 1.05 mol of MnSO4 and 0.3 mol of CuSO4 were added to 1 L of water to obtain a mixed metal sulfate solution; the mixed metal sulfate solution was spray-dried to obtain a mixed metal sulfate powder with a particle size of 3 μm, wherein the air inlet temperature was 220° C. and the air outlet temperature was 130° C.;
[0067] In a compressed air atmosphere, the mixed metal sulfate powder is subjected to a sintering treatment at 1000° C. for 1 h to obtain a mixed metal oxide precursor;
[0068] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate are subjected to a secondary sintering treatment at 1100° C. for 8 hours, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor is 1.03:1, to obtain the single crystal layered oxide positive electrode material.
[0069] Example 6
[0070] The difference between this embodiment and embodiment 1 is that the air inlet temperature of the spray drying is 150° C. and the air outlet temperature is 50° C., and the rest is the same as embodiment 1.
[0071] Example 7
[0072] The difference between this embodiment and embodiment 1 is that the air inlet temperature of the spray drying is 250° C., and the air outlet temperature is 150° C., and the rest is the same as embodiment 1.
[0073] Example 8
[0074] The difference between this embodiment and embodiment 1 is that the mixed metal sulfate powder is sintered once at 500° C. for 3 h in a compressed air atmosphere to obtain a mixed metal oxide precursor. The rest is the same as embodiment 1.
[0075] Comparative Example 1
[0076] This comparative example provides a single crystal layered oxide positive electrode material, and the preparation method is as follows:
[0077] 0.6 mol NiCl2, 1.05 mol FeCl2, 1.05 mol MnCl2 and 0.3 mol CuCl2 are added to 1 L of water to obtain a mixed metal chloride solution; the mixed metal chloride solution is spray-dried to obtain a mixed metal chloride powder with a particle size of 1 μm, such as Figure 4 As shown, it is denoted as NFMCCl2, where the air inlet temperature is 200℃ and the air outlet temperature is 100℃;
[0078] In a compressed air atmosphere, the mixed metal chloride powder is sintered at 900°C for 2 hours to obtain a mixed metal oxide precursor, such as Figure 5 As shown, it is denoted as NFMCO-Cl2;
[0079] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate were subjected to secondary sintering treatment at 900° C. for 8 hours, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor was 1.03:1, to obtain the single crystal layered oxide positive electrode material, recorded as NaNFMC-Cl2.
[0080] The SEM image of the single crystal layered oxide positive electrode material in this comparative example is as follows Figure 6 As shown, it is an oxide positive electrode material with a diameter of 10 μm. In this comparative example, the single crystal layered oxide positive electrode material was tested for the content of each metal atom using inductively coupled plasma (ICP) technology, wherein the proportion of copper ions was significantly lower than the feed ratio, indicating that copper loss occurred during the spray drying process. The test results are shown in Table 2:
[0081] Table 2
[0082] Metal content / at% Ni Fe Mn Cu <![CDATA[NFMCCl2]]> 19.7 37.0 34.9 8.4 <![CDATA[NFMCO-Cl2]]> 19.9 36.1 35.5 8.5 <![CDATA[NaNFMC-Cl2]]> 19.7 36.8 35.1 8.4
[0083] Comparative Example 2
[0084] This comparative example provides an oxide positive electrode material, and the preparation method is as follows:
[0085] Add 0.6 mol of NiSO4, 1.05 mol of FeSO4, 1.05 mol of MnSO4 and 0.3 mol of CuSO4 to 1 L of water to obtain a mixed metal sulfate solution; add 12 L of pure water to a reactor with a volume of 20 L, control the temperature to 58 ° C, control the stirring speed to 380 rpm, pass sodium hydroxide solution to adjust the pH value to 11.30, and continuously pass nitrogen into the reactor to obtain a bottom liquid; pass a mixed metal sulfate solution, sodium hydroxide solution, acetylacetone and citric acid mixed solution into the bottom liquid in parallel for co-precipitation reaction. During the reaction process, measure the pH of the solution and the particle size of the precipitated particles at least once an hour, and observe the morphology of the particles. According to the results, the flow rate of the metal sulfate solution, sodium hydroxide solution, acetylacetone and citric acid mixed solution is continuously adjusted. When the particle size of the precipitated particles is 6 μm, stop the reaction and wash and filter, and obtain a mixed metal oxide precursor after drying;
[0086] In a compressed air atmosphere, the mixed metal oxide precursor and sodium carbonate were subjected to a secondary sintering treatment at 900° C. for 8 hours, wherein the molar ratio of sodium carbonate to the mixed metal oxide precursor was 1.03:1, to obtain the oxide positive electrode material.
[0087] Comparative Example 3
[0088] This comparative example provides a material and a preparation method thereof, wherein the preparation method comprises the following steps:
[0089] 0.6 mol of NiSO4, 1.05 mol of FeSO4, 1.05 mol of MnSO4 and 0.3 mol of CuSO4 are added to 1 L of water to obtain a mixed metal sulfate solution; the mixed metal sulfate solution is spray-dried to obtain a mixed metal sulfate powder with a particle size of 1 μm, wherein the air inlet temperature is 200° C. and the air outlet temperature is 100° C.;
[0090] In a compressed air atmosphere, the mixed metal sulfate powder and sodium carbonate were sintered at 900°C for 10 hours, wherein the molar ratio of sodium carbonate to the mixed metal sulfate powder was 1.03:1. The obtained solid was in the form of a hard block. The XRD spectrum results showed that it was composed of metal oxides and sodium sulfate (such as Figure 7 This is because the sodium ions are recombined with sulfate, and sodium sulfate is difficult to decompose at 900°C, so this method cannot obtain the final oxide positive electrode material.
[0091] Test conditions
[0092] The layered oxide positive electrode materials provided in Examples 1 to 8 and Comparative Examples 1 to 3 were tested, and the testing method was as follows:
[0093] The layered oxide positive electrode materials provided in Examples 1 to 8 and Comparative Examples 1 to 3, the conductive agent Super P, polyvinylidene fluoride and N-methylpyrrolidone are mixed to prepare a positive electrode slurry, which is then scraped onto the surface of an aluminum foil, and then dried, rolled and sliced to obtain a positive electrode sheet;
[0094] The positive electrode sheet was assembled with a polypropylene separator, a lithium sheet and an electrolyte into a 2032-type button cell, wherein the electrolyte consisted of 1 mol / L sodium hexafluorophosphate and a mixed solvent consisting of dimethyl carbonate (DMC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and 1% by mass VC was added.
[0095] The button cell was placed in a blue battery test system and a charge-discharge cycle test was performed using a current density of 0.1C (1C = 240 mA / g).
[0096] The test results are shown in Table 3:
[0097] Table 3
[0098]
[0099] Note: “ / ” in the table means that the performance test cannot be carried out because the oxide positive electrode material cannot be prepared.
[0100] As can be seen from Table 1, by comparing Example 1 with Comparative Example 1, it can be known that the present invention uses a mixed metal sulfate solution with less corrosiveness as a raw material for spray drying pretreatment, so that the prepared mixed metal sulfate powder has uniform composition, which is conducive to the formation of a micron-sized single crystal structure in the subsequent sintering process; and then a large-size single crystal layered oxide sodium ion battery positive electrode material is prepared by two sintering treatments, eliminating the influence of sulfate easily absorbing water and agglomerating, and there is no grain boundary inside the single crystal layered oxide positive electrode material, so that its structural stability is higher than that of the polycrystalline positive electrode material, and at the same time, its discharge capacity is close to that of the positive electrode material prepared using chloride as the raw material.
[0101] Compared with Example 1, Examples 6 and 7 show that the present invention can quickly vaporize and extract the water in the solution by regulating the air inlet temperature and the air outlet temperature of the spray drying, and the sulfate can form spherical particles with uniform composition.
[0102] Compared with Example 1, Example 8 shows that if the temperature of the primary sintering treatment is low, a large amount of sulfate will remain, which is difficult to decompose later.
[0103] By comparing Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that the co-precipitation method and sintering method used in the prior art to prepare the positive electrode material are complicated to operate, and many parameters need to be regulated throughout the process. In addition, there are large differences in the solubility product constants of different metal ions, and it is necessary to select suitable complexing agents and precipitants, so the preparation is relatively difficult; Comparative Example 3 further shows that if the mixed metal sulfate powder and sodium carbonate are directly sintered, the mixed metal sulfate cannot be completely converted into oxides, and sodium sulfate is difficult to decompose at 900°C, so this method cannot obtain the final oxide positive electrode material.
[0104] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a single-crystal layered oxide positive electrode material, characterized in that: The method comprises the following steps: Preparing a mixed metal sulfate solution containing different metal elements; spray drying the mixed metal sulfate solution to obtain a mixed metal sulfate powder; The mixed metal sulfate powder is subjected to a sintering treatment to obtain a mixed metal oxide precursor; The mixed metal oxide precursor and the sodium source are subjected to secondary sintering treatment to obtain the single crystal layered oxide positive electrode material.
2. The method according to claim 1, characterized in that The chemical formula of the single crystal layered oxide positive electrode material is Na a M x N 1-x O2, wherein M is a combination of any two or three of Ni, Fe or Mn, and N is a combination of any one or more of Li, Mg, Al, Si, K, Ca, Ti, V, Cr, Co, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, In, Sn, Sb, W, Ta, Ba, Bi, La, Ce or Eu; 0.7<a≤1.2, 0.8≤x≤1.
3. The method according to claim 1 or 2, characterized in that: The concentration of the mixed metal sulfate solution is 1 mol / L to 4 mol / L, preferably 3 mol / L.
4. The method according to any one of claims 1 to 3, characterized in that The air inlet temperature of the spray drying is 180°C to 220°C, preferably 200°C; Preferably, the outlet temperature of the spray drying is 90°C to 130°C, preferably 100°C.
5. The method according to any one of claims 1 to 4, characterized in that The particle size of the mixed metal sulfate powder is 0.5 μm to 3 μm.
6. The method according to any one of claims 1 to 5, characterized in that The primary sintering process is carried out in an atmosphere containing oxygen; Preferably, the temperature of the primary sintering treatment is 700°C to 1000°C, preferably 900°C; Preferably, the time of the primary sintering treatment is 1 h to 5 h, preferably 2 h.
7. The method according to any one of claims 1 to 6, characterized in that The secondary sintering process is carried out in an atmosphere containing oxygen; Preferably, the secondary sintering treatment is performed at a temperature of 800°C to 1100°C and for a time of 5h to 15h; Preferably, the sodium source includes any one of sodium hydroxide, sodium carbonate, sodium formate or sodium acetate; Preferably, the molar ratio of the sodium source to the mixed metal oxide precursor is (1.01-1.07):
1.
8. A single crystal layered oxide positive electrode material, wherein the single crystal layered oxide positive electrode material is prepared by the method for preparing a single crystal layered oxide positive electrode material according to any one of claims 1 to 7; Preferably, the particle size of the single-crystal layered oxide positive electrode material is 5 μm to 15 μm.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the single crystal layered oxide positive electrode material according to claim 8.
Citation Information
Patent Citations
Monocrystalline sodium battery positive electrode material and preparation method and application thereof
CN118724081A